Mest but Not MiR-335 Affects Skeletal Muscle Growth and Regeneration. - Yosuke Hiramuki; Takahiko Sato; Yasuhide Furuta; M Azim Surani; Atsuko Sehara-Fujisawa (PLoS ONE, 2015)
When skeletal muscle fibers are injured, they regenerate and grow until their sizes are adjusted to surrounding muscle fibers and other relevant organs. In this study, we examined whether Mest, one of paternally expressed imprinted genes that regulates body size during development, and miR-335 located in the second intron of the Mest gene play roles in muscle regeneration. We generated miR-335-deficient mice, and found that miR-335 is a paternally expressed imprinted microRNA. Although both Mest and miR-335 are highly expressed during muscle development and regeneration, only Mest+/- (maternal/paternal) mice show retardation of body growth. In addition to reduced body weight in Mest+/-; DMD-null mice, decreased muscle growth was observed in Mest+/- mice during cardiotoxin-induced regeneration, suggesting roles of Mest in muscle regeneration. Moreover, expressions of H19 and Igf2r, maternally expressed imprinted genes were affected in tibialis anterior muscle of Mest+/-; DMD-null mice compared to DMD-null mice. Thus, Mest likely mediates muscle regeneration through regulation of imprinted gene networks in skeletal muscle.